2013
DOI: 10.1097/01.jnen.0000435847.59828.db
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Gephyrin Immunoreactivity Associated With Alzheimer Disease Pathologic Changes

Abstract: Many neurodegenerative disorders involve the abnormal accumulation of proteins. In addition to the well-known findings of neurofibrillary tangles and β-amyloid plaques in Alzheimer’s disease, here we show that abnormal accumulations of gephyrin, an inhibitory receptor anchoring protein, are highly correlated with the neuropathologic diagnosis of AD (odds ratio of 72.7; p = 6.844 × 10−6 by Fisher’s exact test, n = 17 AD and n = 14 control cases). Furthermore, the gephyrin accumulations are specific for AD and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Membrane-enriched protein extracts were prepared as previously described [12] from frozen frontal cortical tissue of 4 AD and 5 control brains that had been included in immunohistochemistry studies. Briefly, approximately 200 mg of brain tissue was homogenized in lysis buffer (10mM Tris base/hydrochloride, 10mM EDTA, pH 7.4) with 1× protease inhibitor cocktail (#13006200; Roche, San Francisco, CA) while on ice followed by agitation with metallic beads and sonication (4 × 5-s pulses with 15 s breaks to avoid overheating).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane-enriched protein extracts were prepared as previously described [12] from frozen frontal cortical tissue of 4 AD and 5 control brains that had been included in immunohistochemistry studies. Briefly, approximately 200 mg of brain tissue was homogenized in lysis buffer (10mM Tris base/hydrochloride, 10mM EDTA, pH 7.4) with 1× protease inhibitor cocktail (#13006200; Roche, San Francisco, CA) while on ice followed by agitation with metallic beads and sonication (4 × 5-s pulses with 15 s breaks to avoid overheating).…”
Section: Methodsmentioning
confidence: 99%
“…The total protein samples were incubated with anti-Kv1.3 rabbit polyclonal antibody (APC 101, Alomone labs, 1 : 1000) and anti-α-tubulin (Cell Signaling, #3873,1 : 1000) for 24 h. Membrane fraction samples were probed with anti-Kv1.3 and anti-Na/K ATPase α1 subunit mouse monoclonal antibody (Millipore #05–369,1 : 1000) for 2h. After 3 washes, fluorescent secondary antibodies (anti-mouse IgG IRDye ® 800 conjugate, Rockland, 1 : 20,000 and anti-rabbit IgG Alexa Fluor ® 680 conjugate, Invitrogen) were added for 1 h. An Odyssey Scanner (LI-COR, Lincoln, NE) was used to visualize proteins labeled and densitometric analysis of gel bands was performed using ImageJ as previously described [12]. Kv1.3 protein expression was normalized to Na/K ATPase α1 subunit (for membrane fractions) and both absolute and mean densitometric units were compared across both groups after three replicative experiments (unpaired two-tailed Student’s T -test).…”
Section: Methodsmentioning
confidence: 99%
“…Gephyrin levels are reduced in the brains of patients suffering from Alzheimer's disease, but its direct involvement in this disorder has not yet been fully explored. 114,115 Intriguingly, temporal lobe epilepsy has been linked to abnormal operation of the gephyrin splicing machinery. 113 More specifically, cellular stresses (e.g., alkalosis) increase the proportions of gephyrin splice variants lacking exons encoding the G domain, potentially altering the activity of gephyrin clustering.…”
Section: Synaptic Functions Of Gephyrinmentioning
confidence: 99%
“…Importantly, aberrant regulation of this gene has been associated with a host of complex diseases. Dysfunction in the regulation of gephyrin expression levels and/or isoform production has been implicated for Alzheimer’s disease (AD) 38 40 , epilepsy 9 , 41 , 42 , autism 10 , schizophrenia 10 , 43 , hyperekplexia 13 , and chorein deficiency 44 . Gephyrin levels are significantly reduced in AD brains 39 , and the normally strong correlations between gephyrin production and the abundances of the six most common GABA subunits is corrupted in AD brains 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Gephyrin levels are significantly reduced in AD brains 39 , and the normally strong correlations between gephyrin production and the abundances of the six most common GABA subunits is corrupted in AD brains 38 . It has also been observed that abnormal accumulations of low-molecular weight gephyrin plaques overlap beta-amyloid plaques 40 . Epilepsy is characterized by abnormal excessive excitatory neuronal activities, and dysfunction of inhibitory neurons and/or down-regulation of inhibitory circuits may be the underlying cause 41 .…”
Section: Discussionmentioning
confidence: 99%